A comparative study of Chinese and U.S. news coverage of the 2014 Hong Kong uprising - Meng, Chao (Kansas State University, 2015)
Background: During the 2014 Hong Kong protests, with the growing concern of various perspectives in the international media, news coverage, as the main source of information transportation has become an issue of research interest. According to framing theory, for a certain event, media is likely to place it within a field of meaning. Furthermore, the message meaning, framed by media, influence audience’s information processing. Different media organizations might have different perspectives on framing same event. This study examined how Chinese news coverage and U.S. news coverage framed an event. Method: A quantitative content analysis was conducted among a sample of 152 news stories from China Daily and The New York Times. All the stories from August 17th 2014 to January 8th 2015 were analyzed to determine whether the 2014 Hong Kong protest was framed by China Daily and The New York Times differently. The code sheet was structured with key variables derived from former published articles. Furthermore, the categories of main issue and secondary issue came from pre-tests with another co-coder. Data analysis was conducted with frequency counts, cross tabulations and Pearson’s chi-square analysis in SPSS. Results: Findings suggested that news coverage of China Daily focused on the issues of politics and protest, as well as did the coverage of The New York Times. However they have significant differences on framing of history, profiles of protesters and others. The findings suggested that the China Daily and The New York Times have significant differences on overall bias in terms of Pro-change, Anti-change and Neutral. Conclusion: Samples in this study, as prosperous news organizations with the reputation and resources to conduct fair reporting and to set journalistic standards in China and the United States respectively, represented most perspectives in general. According to different factors of national interest, political ideology and history, Chinese news coverage and U.S. news coverage have significant differences on framing the issues and overall bias.
Keywords: Newspaper; Framing; Politics; China; United States; Journalism; Journalism (0391)